Inflammation Protocols - Winyard, Paul G.; Willoughby, Derek A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2003)
Because inflammation is involved in many chronic human diseases, its proper understanding may provide important clues to new therapeutic targets. In Inflammation Protocols, highly skilled experimenters present key techniques for the multidisciplinary study of inflammation in such conditions as inflammatory bowel disease, rheumatoid arthritis, renal disease, and cardiovascular disease. Described in step-by-step detail to ensure experimental success, the techniques are focused on the research and development of potential new antiinflammatory drugs in active target areas. The protocols are suitable for many current areas of drug discovery research, including transcription factors, cytokines, adhesion molecules, cyclooxygenase-2 (COX-2) inhibitors, free radicals, nitric oxide synthases, complement activation, angiogenesis, wound healing, immune rejection, and metalloproteinases. The methods provide in vitro systems for studying inflammation, in vivo models, and relevant pharmacodynamic measurements for the assessment of antiinflammatory compounds. Each protocol contains notes about potential pitfalls and tips on how to avoid failure. Overview chapters at the start of each section review the significance and potential limitations of the protocols presented. Cutting-edge and highly practical, Inflammation Protocols offers experimental and clinical researchers a premier collection of readily reproducible techniques not only for evaluating inflammatory disease processes, but also for the discovery of new drugs for treating chronic human inflammatory diseases today.
In Vitro Systems for Studying Aspects of the Inflammatory Response and Testing Antiinflammatory Drugs -- Key Stages in the Acute Inflammatory Response and Their Relevance as Therapeutic Targets -- I?B Kinase and NF-?B Signaling in Response to Pro-Inflammatory Cytokines -- Screening for Inhibitors of Transcription Factors Using Luciferase Reporter Gene Expression in Transfected Cells -- Adhesion Molecule Expression on Cytokine-Stimulated Human Endothelial Cells -- Phagocytosis by Inflammatory Phagocytes -- Cytosolic Ca2+ Measurement and Imaging in Inflammatory Cells -- Detection and Visualization of Oxidase Activity in Phagocytes -- Measurement of Complement Activation -- Measurement of Matrix Metalloproteinase Activities in the Medium of Cultured Synoviocytes Using Zymography -- Measurement of Aggrecanase-Generated Interglobular Domain Catabolites in the Medium and Extracts of Cartilage Explants Using Western Blot Analysis -- In Vitro Model of Human Articular Cartilage Degradation -- In Vivo Models of Inflammation -- In Vivo Models of Inflammation -- Carrageenan-Induced Paw Edema in the Rat and Mouse -- Pleural Models of Inflammation -- Models of Acute Inflammation in the Ear -- Migration of Specific Leukocyte Subsets in Response to Cytokine or Chemokine Application In Vivo -- Inflammatory Joint Disease -- The Assessment of Inflammation, Cartilage Matrix, and Bone Loss in Experimental Monoarticular Arthritis of the Rat -- Collagen-Induced Arthritis -- Air-Pouch Models of Inflammation and Modifications for the Study of Granuloma-Mediated Cartilage Degradation -- Quantitative Analysis of Angiogenesis Using the Murine Chronic Granulomatous Air Pouch -- Models of Coronary Artery Occlusion and Reperfusion for the Discovery of Novel Antiischemic and Antiinflammatory Drugs for the Heart -- Assessment of Anticolitic Drugs in the Trinitrobenzene Sulfonic Acid (TNBS) Rat Model of Inflammatory Bowel Disease -- An In Vivo Model of Ischemia/Reperfusion and Inflammation of the Kidneys of the Rat -- In Vivo Models of Inflammation -- Wound Healing -- Pharmacodynamic Endpoints in Experimental Models and In Clinical Studies in Humans -- An Iconoclastic Approach to Pharmacodynamics in Model Systems: Their Relevance to Humans -- A Reply to “An Iconoclastic Approach to Pharmacodynamics in Model Systems: Their Relevance to Humans“ -- Quantifying Inflammation In Vivo Using Radiolabeled Antibodies and Leukocytes -- Immunoperoxidase Histochemistry for the Detection of Cellular Adhesion Molecule, Cytokine, and Chemokine Expression in the Arthritic Synovium -- Roles of Nitric Oxide and Superoxide in Inflammation -- Analysis of Nitrite and Nitrate in the Study of Inflammation -- In Vivo Assays for COX-2 -- Measurement of 8-epi-PGF2? as a Marker of Lipid Peroxidation In Vivo by Immunoaffinity Extraction and Gas Chromatography-Mass Spectrometry -- Laboratory Assessment of the Acute Phase Response -- Assays of Matrix Metalloproteinases (MMPs) and MMP Inhibitors.
Keywords: Immunology; Immunology